Gestión directiva para la prevención y abordaje de delitos sexuales en los estudiantes de la escuela de educación básica “Alejandro Dávalos Calle” ubicado en la parroquia San Marcos, cantón Salcedo, en el periodo académico 2014 – 2015 - Andagana Estrada, Geovanny Patricio (2015)
Preventing and sexual abuse in families, educational institutions and society in general is of vital importance, because every human being should have to a goodlife outof suffering, impotence and fear, especially those vulnerable people as: children and adolescents. Prevention starts at home, from early childhood when parents teach their children the name correct of their private parts, taking care of their body, like the greatest treasure that possess, when someone give them weapons to identify if anyone can be a potential aggressor, how to avoid being a victim of sexual violence. Therefore it proposed several strategies for improving executive management on preventing and sexual abuse in schoolstudents, and determine the causes, effects of the problem at structuring of a proposal methodological guide about prevention and survey of sexual offenses, giving solutions to decrease the problem, with this proposal is essential to educate teachers staff, parents and new generations how to avoid becoming a victim of a sexual offense.